2022
DOI: 10.1186/s12871-022-01939-4
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic outcomes of tramadol alone and in combination with Butorphanol or Flurbiprofen Axetil after cesarean section: a retrospective study with propensity score matching analysis

Abstract: Background The Society for Obstetric Anesthesia and Perinatology recommends a multimodal analgesia regimen for cesarean delivery analgesia. This study aimed to compare the analgesic effects of tramadol alone and combined with butorphanol or flurbiprofen axetil after a cesarean section. Methods We performed a retrospective analysis based on the electronic medical records of a teaching hospital in China from January 2018 to January 2020. We collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In our study, women undergoing cesarean delivery still experienced obvious postoperative pain, despite receiving routine postoperative PCIA; the incidence of inadequate postoperative analgesia was as high as 89.85%, which is similar to that reported by Borges et al, 24 but much higher than that reported by Bekele et al 25 Another study of 2323 Chinese women who underwent cesarean section showed that 59.1% of women had inadequate analgesia 48 h after surgery, despite using a mixture of tramadol and furoprofen acetate. 3 One reason for our result is that we used a 24-h activity NRS score of ≥4 to assess inadequate analgesia, and the analgesia score at 24 h was higher than that at 48 h, thereby the incidence of analgesia is higher. Furthermore, the numerical pain scale used was subjective, and the results might differ in people with different ethnic and cultural backgrounds.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our study, women undergoing cesarean delivery still experienced obvious postoperative pain, despite receiving routine postoperative PCIA; the incidence of inadequate postoperative analgesia was as high as 89.85%, which is similar to that reported by Borges et al, 24 but much higher than that reported by Bekele et al 25 Another study of 2323 Chinese women who underwent cesarean section showed that 59.1% of women had inadequate analgesia 48 h after surgery, despite using a mixture of tramadol and furoprofen acetate. 3 One reason for our result is that we used a 24-h activity NRS score of ≥4 to assess inadequate analgesia, and the analgesia score at 24 h was higher than that at 48 h, thereby the incidence of analgesia is higher. Furthermore, the numerical pain scale used was subjective, and the results might differ in people with different ethnic and cultural backgrounds.…”
Section: Discussionmentioning
confidence: 96%
“… 2 Due to the influence of postpartum contractions and surgical incisions, women undergoing cesarean section often experience severe postoperative pain. 3 , 4 However, despite the numerous measures developed to manage postoperative pain, inadequate analgesia following cesarean section was common, with an incidence of 68–76%. 5 , 6 Inadequate pain treatment and a high risk of severe acute pain could be possible explanations.…”
Section: Introductionmentioning
confidence: 99%